Perceptions and attitudes towards shoulder padding and shoulder injury in rugby union - Hughes, A.; Carré, M.; Driscoll, H. (Journal of Science in Sport and Exercise, 2022)
Purpose: To develop an understanding of the role of shoulder padding in rugby union by investigating player perceptions and attitudes towards shoulder padding and extending research into shoulder injuries in rugby. Methods: An online survey was distributed to past and current rugby players over 13 years old in 2018. Questions related to the participants` demographic, attitudes to shoulder padding and shoulder injury history. Results: Six hundred and sixteen rugby players responded to the survey; 66.1% of respondents had worn shoulder padding at some point. The age group 24-29 years old (DeltaR2 = 0.03, B = - 0.53, P = 0.015) had an inverse association with padding effectiveness while playing experience groups 1-2 years (DeltaR2 = 0.03, B = 0.8, P = 0.032), 3-5 years (DeltaR2 = 0.03, B = 0.70, P = 0.002) and 6-9 years (DeltaR2 = 0.03, B = 0.41, P = 0) had a positive association. There are 37.1% of respondents considering shoulder padding to be effective at preventing cuts and abrasions with 21.9% finding it very effective; 50.3% considered it to be effective or very effective (9.7%) at preventing contusion; 45.5% wore padding for injury prevention, while 19.2% wore padding to protect from reoccurring injury. Sprain/ligament damage (57.5%) and bruising (55.5%) were the most commonly reported injuries. Conclusions: The primary reason for wearing shoulder padding was as a means of injury prevention. Research should focus on quantifying the injury preventive capabilities of shoulder padding. Bruising, cuts and abrasion injuries to the shoulder are prevalent presenting new findings that these injuries are underreported.